Risk and Protective Factors of Child-to-Parent Violence: A Comparison Between Physical and Verbal Aggression - Beckmann, Laura; Bergmann, Marie Christine; Fischer, Franziska; Mößle, Thomas (Journal of interpersonal violence, 2021)
Child-to-parent violence (CPV) is a social problem that remains vastly understudied compared with other forms of family violence. The aim of this study is to identify family and child risk and protective factors of CPV, and to investigate whether they differentially predict physical and verbal parent-directed violence among boys and girls. Predictors include parenting behavior during childhood (physical and verbal violence, warmth, monitoring) and respondents’ individual characteristics (suicidal ideation, self-control, problematic substance use). Data were examined from a large representative sample of ninth graders (N = 6,444) in Lower Saxony, Germany. Bivariate analyses showed that female adolescents were more likely to aggress verbally, while no gender differences were found for physical CPV. Multilevel logistic regression models revealed that direct experiences of parental physical and verbal violence during childhood were among the strongest predictors of physical and verbal CPV, both among males and females. While parental monitoring was not significantly associated with CPV, parental warmth protected girls from physical parent-directed aggression. Furthermore, high self-control was protective against verbal CPV as well as boys’ physical CPV, while problematic substance use predicted physical violence toward parents in both sexes but only boys’ verbal CPV. Suicidal ideation was a risk factor of aggression in males only. Except for parental warmth, the importance of risk and protective factors did not substantially vary across child gender. These findings broaden our understanding of different family and child-related factors that either promote or prevent CPV. Specifically, they point to the importance of the parenting context and especially harsh discipline practices for the occurrence of both physical and verbal CPV.